IMPROVING LEARNING OUTCOMES OF MATERIALS ON THE DANGERS OF SMOKING FOR HEALTH THROUGH AUDIO VISUAL MEDIA IN CLASS V STUDENTS OF SD NEGERI 101776 SAMPALI - Arfan Hakim Pane; Budi Valianto (Indonesia Sport Journal, 2021)
This study aims to determine the improvement of learning outcomes of hidden materials for health through audio visual media in fifth grade students of SD Negeri 101776 Sampali. The research method used is Classroom Action Research. The research subjects were fifth grade students of SD Negeri 101776 Sampali with a total of 28 students. Based on the initial test of learning outcomes of ability in the dangers of smoking for health, the percentage of students (14%) is 4 students out of 28 students. After the research, the learning outcomes test in cycle I and cycle II was carried out. And then in the second cycle of learning outcomes test, students experienced an increase in learning outcomes, namely 25 students (89%) had achieved learning mastery, while 3 students (11%) had not achieved learning mastery. Based on the results of data analysis, it can be obtained that audio-visual media can influence and improve learning outcomes of smoking material for health in fifth grade students of SD Negeri 101776 Sampali.Keywords: Dangers of Smoking, Learning Outcomes, Audio Visual Media